RET fusion driven (RETfus+) non-small cell lung cancer: a comprehensive genomic profiling study with histologic correlation - Prashanth Ashok Kumar; Michael Connolly; Alina Basnet; Dean Pavlick; Richard Huang; Steven Graziano; Jeffrey Ross; Jeffrey Ross; Jeffrey Ross (Frontiers in Oncology)
BackgroundFusion of the RET gene resulting in clinically significant Genomic Alteration (GA) occur in 1-2% of NSCLC in the United States and has emerged as a major target for RET inhibitors which are first line treatment options in the Stage 4 setting. RET fusions have also been well-described as acquired resistance mutations in cases of EGFR-driven NSCLC treated with anti-EGFR tyrosine kinase inhibitors including erlotinib and osimertinib. The aim of this study was to determine whether RET fusion positive (RETfus+) NSCLC represents a unique histologic subtype of the disease with a unique genomic profile.MethodsWe selected 503 of 72,596 (0.7%) total NSCLC that were reported as RETfus+ from the Foundation One database. The cases were centrally evaluated for predominant histology and underwent hybrid capture based CGP to evaluate diverse GA. Cases with EGFR mutations were excluded. PD-L1 expression was determined by Immunohistochemistry (IHC) (Dako 22C3) with Tumor Proportion Score (TPS) ≥50% = high expression. For statistical comparisons, the false discovery rate was corrected using Benjamini/Hochberg adjustment.ResultsPotentially targetable GAs found less frequently in the RETfus+ group included BRCA1, BRAF, FGF12, FGFR1, KEAP1, KMT2D, KRAS, MDM2, MET, NF1, NSD3, PIK3CA, RB1, AND TP53. The presence of HRD, APOBEC and Tobacco gene signatures were also lower in frequencies in the RETFus+ NSCLC cases. SETD2 was the only GA found to be higher in the RETfus+ group. While markers predictive of checkpoint therapy response including TMB high level was more frequent in the RETfus- cases, PD-L1 high expression was more in RETfus+ samples. Surgical pathology analysis revealed that the high grade solid non-acinar pattern at 32% was the most frequent histologic subtype.ConclusionsRETfus+ NSCLC features a unique genomic signature which can further impact therapy selection. With recent expanded approval of more specific RET kinase targeting inhibitors (selpercatinib and Pralsetinib) in the pan-cancer treatment setting, further study of RETfusion+ NSCLC histology and genomic/biomarker status appears warranted.